2014
DOI: 10.1136/bmjopen-2013-003768
|View full text |Cite
|
Sign up to set email alerts
|

Validity of instruction leaflets for parents to measure their child's weight and height at home: results obtained from a randomised controlled trial

Abstract: ObjectivesTo compare the validity of parent-reported height, weight and body mass index (BMI) values of children (aged 4–10 years), when measured at home by means of newly developed instruction leaflets in comparison with simple estimated parental reports.DesignRandomised controlled trial with control and intervention group using simple randomisation.SettingBelgian children and their parents recruited via schools (multistage cluster sampling design).Participants164 Belgian children (53% male; participation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 16 publications
1
22
1
Order By: Relevance
“…Data on height and weight were based on the information given by parents. However, Huybrechts et al have shown that parents can give reliable information about height and weight of their children if they received instructions on how measurements should be performed [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Data on height and weight were based on the information given by parents. However, Huybrechts et al have shown that parents can give reliable information about height and weight of their children if they received instructions on how measurements should be performed [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The parents were thoroughly instructed how to measure their own body height and weight, as well as the height and weight of their offspring according to the illustrated instruction leaflets for home measurement. Parental home measurement of children's and adolescents' body height and weight [39][40][41][42] is considered to be sufficiently valid for calculating the BMI for a subsequent identification of childhood obesity [39,40]. The chronological age of all family members was calculated from the date of birth until the starting day of the PA monitoring.…”
Section: Procedures and Measurementmentioning
confidence: 99%
“…Another potential limitation could be the home measurement of body weight and height of family members. However, parental home measurement of their children' weight and height according to researchers' instruction sheets are sufficiently accurate compared with laboratory measurement [40] for subsequent BMI calculations and classification of overweight and obesity [63], for example according to the WHO percentile growth charts. Moreover, none of the family members was given the cut-off values to classify body weight levels according to the WHO percentile growth charts for obesity classification.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…The parents were thoroughly instructed how to measure their own body height and weight, as well as the height and weight of their offspring, according to the illustrated instruction lea ets for home measurement. Parental measurement of the body height and weight of their offspring at home [39][40][41][42] seems to be a su ciently valid method to identify overweight/obesity according to the calculated BMI compared with objective or laboratory/researcher measurements [39,40,43]. Although self-reported body height and weight is a widely used method for determining underweight, normal body weight, overweight, and obesity, previous studies point to possible inaccuracies compared with laboratory/researcher measurements and the absence of a uniform measurement consensus [43][44][45][46].…”
Section: Procedures and Measurementmentioning
confidence: 99%
“…Another potential limitation could be the home measurement of the body weight and height of family members. However, parental home measurement of children's weight and height according to researchers' instruction sheets is su ciently accurate compared with laboratory measurement [40] for subsequent BMI calculations and the classi cation of overweight and obesity [66], for example according to the WHO percentile growth charts. Moreover, none of the family members was given the cut-off values to classify body weight levels according to the WHO percentile growth charts for the classi cation of obesity.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%